Dynamics Study of the OH + O2 Branching Atmospheric Reaction. 2. Influence of Reactants Internal Energy in HO2 and O3 Formation - Caridade, P. J. S. B. (2001)
The effect of reactants vibrational and rotational excitation on products (HO2 + O and O3 + H) formation is investigated for the title reaction by using the quasiclassical trajectory method and the realistic double many-body expansion (DMBE) potential energy surface for ground-state HO3. It is shown that it can be a potential source of ozone in the upper atmosphere.